Determining the factors that influence the sales volume: a case study of MVBD, Menara Kuala Lumpur / Nuradlina Che Min - Che Min, Nuradlina (Faculty of Business and Management, 2006)
This study examines the factors of marketing mix that influence the sales volume of products and services offered. Specifically, the study examines the association between price; service, and promotional activities with sales volume. Delivering service quality is an essential strategy for success and survival in today's competitive environment. Furthermore, price is the determining key that could and would seal consumer's decision. A structured questionnaire was developed and administered to a total of 49 customers via telephone interviews. Two types of data analysis, descriptive analysis and correlation coefficient, were used for this research. The result provides support for three out of four objectives that were examined.